2016
DOI: 10.1080/10426914.2016.1198039
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on performance of abrasive water jet in machining hybrid composites

Abstract: For machining of composites, Abrasive Water Jet Machining is widely employed. For assembly of the machine tool structure, production of slots is essential. In this paper, abrasive water jet machining of composite laminates was experimentally investigated for various cutting parameters in terms of average surface roughness (R a ) and kerf taper (K t ).By generating a response surface model, the experimental values obtained for quality characteristics (R a and K t ) were empirically related to cutting parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(27 citation statements)
references
References 13 publications
0
27
0
Order By: Relevance
“…us, with the development of water jet technique, an abrasive water jet (AWJ) assistance, as a new method, has been developed in hard rock mechanical cutting and drilling [14]. Selvam et al [15] observed abrasive water jet machining of composite laminates experimentally for various cutting parameters in terms of average surface roughness and kerf taper. By generating a response surface model, the experimental values obtained for quality characteristics were empirically related to those of cutting parameters.…”
Section: Introductionmentioning
confidence: 99%
“…us, with the development of water jet technique, an abrasive water jet (AWJ) assistance, as a new method, has been developed in hard rock mechanical cutting and drilling [14]. Selvam et al [15] observed abrasive water jet machining of composite laminates experimentally for various cutting parameters in terms of average surface roughness and kerf taper. By generating a response surface model, the experimental values obtained for quality characteristics were empirically related to those of cutting parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, this supports the choice of hybrid composite in this present work. Nevertheless, Selvam et al [21] investigated the performance of AWJ in machining (slotting) hybrid composite sample. This sample was a conventional hybrid composite laminate, comprised of both bidirectional E-glass and carbon fabrics (synthetic, not natural or sustainable fibres) with epoxy resin.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the high energy consumption and low efficiency of the traditional waterjet limited its application. To make better use of waterjet technology and lower its energy consumption, various kinds of waterjets have been invented, such as the pulsed waterjet [6,7], abrasive waterjet [8], cavitating waterjet [9,10], and so on. As environmentally friendly technologies, the pulsed waterjet can take advantage of the water hammer effect [11], and the cavitating waterjet can harvest the energy of cavity collapse [9,12]; both of them can significantly lower the energy consumption during the working process.…”
Section: Introductionmentioning
confidence: 99%